Biomass and stable carbon isotope distributions in the Amazon plume region - Alriyami, Zainab; Montoya, Joseph P. (Frontiers in Marine Science, 2024)
We investigated the distribution, C:N elemental ratio, and δ¹³C of suspended particulate carbon in the surface and upper 100 m of the water column during three seasons in areas of the Western Tropical North Atlantic influenced by the Amazon River Plume: the Spring high flow period (KN197 Cruise, May-June), the late Summer period of reduced flow (AT2104 cruise, July), and the low flow period in the Fall (MV1110 cruise, Sept-Oct). We used a habitat delineation method to examine spatial and temporal variability in our biogeochemical parameters. We found the highest biomass concentration ([PC]=259.7 µM), high C:N ratio (13.6), and the most negative δ¹³C (-26.8 ‰) in the area proximate to the river mouth during the late summer cruise. We measured elevated [PC] (64.5 µM), C:N ratios (14.1), and δ¹³C (max -15.7 ‰) in the plume core habitats during the peak flow season, reflecting the impact of both the outflow and in situ phytoplankton production. We found that the western margin of the plume had relatively higher biomass, C:N ratios, and organic matter more enriched in 13C than the east margins. In our work area, oceanic waters had the lowest [PC] (1.3 µM), a C:N ratio higher than the Redfield ratio (6.6), and an average δ¹³C of -22 ‰. We explored the relationships between PC and Chla, and δ¹³C and C:N ratio to estimate the contribution of phytoplankton production and terrigenous sources to the suspended particulate carbon pool. We found terrestrial and detrital sources contributing more to the organic matter of the river mouth area. However, the contribution of phytoplankton and living sources dominate most of our study area in all seasons. Our findings emphasize the role of the Amazon River Plume in enhancing biomass and productivity of the WTNA and the biogeochemical dynamic of the carbon cycle.